ANALISIS RASIO UNTUK MENGUKUR KINERJA KEUANGAN PEMERINTAH PROVINSI JAWA TIMUR PER-KABUPATEN/KOTA TAHUN ANGGARAN 2012-2021 - Siagian, Ester Katerina P.; Fadjar, Nurman Setiawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research, which was conducted in East Java, attempts to identify and analyze the financial performance of regional government during the 2012-2021 fiscal years. This descriptive quantitative research uses secondary data, summarized from the 2012-2021 period budget. The population are 38 regencies and cities in East Java. This study finds that 5.2% of the regions are independent (i.e. Surabaya city and Sidoarjo regency), 2.6% are toward independency (i.e. Gresik regency), 26% are in consultative relationship pattern (i.e. Tulungagung regency, Pasuruan regency, Mojokerto regency, and Madiun city), while the rest are having low independency or in instructive relationship pattern. This study also finds that the local financial management of the 38 regencies and cities in the province is very effective; the ration between the targeted and realized local own-source revenues is higher than 100%. The financial efficiency of the regencies and cities during the research period is not quite efficient. In fact, Pacitan regency, Sidoarjo regency, and Pamekasan regency are inefficient in the said matter. Furthermore, it was also found that the local budgets of the 38 local governments during the 2012-2018 were mostly allocated to direct expenditures. However, during the 2019-2021 period, following the enactment of government regulation number 12 of 2019 concerning the changes in local own-source revenue realization format, the local governments’ expenditures were dominated by employee expenditures. Finally, this study also finds that, during the last decade, the local own-source revenues of the said local governments were not stable and tended to decline.